Manpower Development and Employee Commitment in Selected Local Government Areas in Delta State - Okereka, Onofere Princewill; Abasili, Olisa Kizito (LPPM Universitas Malikussaleh, 2023)
Nigerian local governments have been investing in employee training and manpower development over the years to improve the institutions' overall performance and level of dedication. This is because it is acknowledged that training and workforce development play a critical role in achieving organizational goals and objectives. Thus, in a few Delta State local government units, this study looked at the relationship between employee commitment and manpower development. Using a self-administered questionnaire, 390 employees provided data, and the Taro Yamane method was used to calculate the sample size. With the help of the Statistical Package of Social Science (SPSS) version 23.0, the collected data was analyzed using percentages and frequency, Pearson's correlation coefficient, and linear and multiple regression. The results showed that employee commitment (affective commitment, continuance commitment, and normative commitment) was highly influenced by manpower development. The study came to the conclusion that employee commitment and manpower development increase organizational effectiveness. Therefore, in order to effectively improve employee performance and organizational effectiveness, policies that enhance workplace commitments and duties must be promoted. Therefore, among other recommendations made by the study, the management of Delta State's Local Government Councils should set up programmes for staff members' professional and personal growth. This means making long-term plans for career development initiatives. Employee commitment (affective, continuance, and normative commitments) will be greatly increased as a result, and employees will be able to meet their goals.